Penerapan Fault Tree Analysis (FTA) dan Siklus PDCA untuk Meminimalkan Buah Restan pada Proses Pengangkutan Tandan Buah Segar (TBS) di PT XAY Sumatera Utara - Dewi Jelita Siagian; Suprayetno Marbun; Indira Ruth Septarini (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The transportation of Fresh Fruit Bunches (FFB) is a crucial stage in the palm oil production process as it directly affects the quality of raw materials delivered to the mill. Delays in FFB transportation can lead to the occurrence of restan fruit, namely FFB that are not transported on the harvesting day, which subsequently results in an increase in free fatty acid (FFA) levels, a decline in Crude palm oil (CPO) quality, and reduced operational efficiency. This study aims to identify the main factors causing restan fruit during the FFB transportation process and to design process improvement measures using the Fault Tree Analysis (FTA) method and the Plan–Do–Check–Act (PDCA) cycle. FTA is applied to systematically map the cause-and-effect relationships of restan fruit problems to determine their root causes, while the PDCA cycle is implemented as a continuous improvement approach based on the results of the FTA analysis. This research was conducted at PT XAY Sumatra Utara Unit, with a focus on FFB transportation activities that potentially lead to restan fruit. The results indicate that the primary causes of restan fruit include limited availability of transport vehicles, poor plantation road conditions, suboptimal route and transportation scheduling, and ineffective coordination among operational units. The implementation of the PDCA cycle based on FTA findings is expected to minimize the occurrence of restan fruit, improve the timeliness of FFB transportation, and enhance the company’s operational performance on a sustainable basis.